'Everyone here wants everyone else to get better': The role of social identity in eating disorder recovery. (26th September 2016) - McNamara, Niamh; Parsons, Harriet
Abstract : Retention of a positively valued illness identity contributes to poor outcomes for individuals with eating disorders (EDs). Consequently, dis‐identification from the illness identity and the adoption of a recovery identity are vital for successful recovery. While social identity processes have been shown to influence ED maintenance, their role in recovery is rarely considered. This study explores how a sense of shared identity helps individuals with EDs manage their condition and promotes recovery. Transcripts from 18 online support sessions involving 75 participants were thematically analysed. Our findings suggest that the illness identity initially operates as a social identity that forms the basis for connections with similar others. For those wishing to recover, identity‐based support is then perceived to be more effective than that found outside the group. Online interactions also facilitate construction of a new shared recovery identity which promotes a shift from the illness identity as a primary source of definition and endorses group norms of illness disclosure and treatment engagement. While in the clinical literature, ED identity is seen as problematic and interventions are targeted at challenging an individual's self‐concept, we suggest that interventions could instead harness identity resources to support a transition to a recovery identity.